Bandwidth enhancement techniques for probe-fed microstrip patch antennas - Zou, Xinlei (University of Ottawa (Canada), 2005)
Many bandwidth enhancement techniques for microstrip patch antennas have been developed since the 1970's. Except for an IEEE collection of reprints which appeared in 1995, relatively little work has been done to review and categorize these techniques. As a result, the published research and design of broadband microstrip antennas has become somewhat unsystematic. In this thesis, papers on broadband microstrip antennas have been reviewed. Using full-wave electromagnetic simulation, the important performance parameters such as the bandwidth, realized gain, antenna efficiency, radiation efficiency and radiation patterns of broadband microstrip patch antennas have been considered. Based on these results, bandwidth enhancement techniques have been categorized in two broad classes, namely those applicable when electrically-thick low-permittivity substrates are used, and those applicable to electrically-thin high-permittivity substrates. These broad classes have been sub-divided into several sub-classes in a structured manner that aids the understanding of the bandwidth enhancement methods. A summary of these techniques, linked to a comparison of resulting microstrip patch antenna performance obtained from full-wave analysis of the sub-classes, is provided. It is also shown, through a specific example, how the increased understanding afforded by this categorization can lead to the development of new broad bandwidth geometries that can offer some advantages over existing ones.
Keywords: Engineering, Electronics and Electrical.